A colorimetric sensor for protamine detection based on the self-assembly of gold nanorods on graphene oxide. (16th May 2019) - Wiriyachaiporn, Natpapas; Srisurat, Petpimon; Cherngsuwanwong, Jarumeth; Sangsing, Natcha; Chonirat, Jaruwan; Attavitaya, Sahawat; Bamrungsap, Suwussa
Abstract : Here, we report a simple colorimetric detection method for the determination of protamine based on the self-assembly of gold nanorods (AuNRs) on graphene oxide (GO). Abstract : Here, we report a simple colorimetric detection method for the determination of protamine based on the self-assembly of gold nanorods (AuNRs) on graphene oxide (GO). Within the system, the positively charged AuNRs could adsorb electrostatically on negatively charged GO, resulting in AuNR aggregation and color change from red to dark purple. Upon the addition of protamine, AuNRs were freely dispersed and remained red in color due to the strong adsorption between GO and protamine, preventing AuNRs from aggregation. The formation of GO–AuNR complexes and dispersed AuNRs was confirmed by transmission electron microscopy. The degree to which AuNRs aggregated was inversely proportional to the amount of protamine present in the system. The change in the absorption maxima of AuNRs in the presence of protamine was monitored. Using this simple system, under optimized conditions, protamine could be detected in the range of 100–700 ng mL −1 ( R 2 = 0.9683). Based on 3 σ / s, where σ is the standard deviation of blank and s is the slope of the linear graph, the system could detect protamine as low as 6.3 ng with the sample volume of 100 μL. The system also demonstrated good selectivity towards interferences from other related physiological molecules including human serum albumin, hemoglobin protein, glucose, essential ion species, and other positively charged drugs.